Factores de riesgo asociados al fracaso de una Timpanoplastia – Hospital Víctor Lazarte Echegaray - Silva Gamarra, Silvia Vanessa (2020)
Determine if the location of the perforation, the size of the perforation and the type of graft used are risk factors for tympanoplasty failure. Background: Chronic Otitis Media (COM) is one of the most frequent otological infectious diseases in the environment, and its surgical treatment, depending on the magnitude of the lesions, may be more conservative or be more aggressive, so the identification of the possible factors that influence the operative outcome is essential. Method: A case-control study (longitudinal, retrospective, observational) will be carried out with indirect risk calculation for the different variables, using the clinical history of all post-operated tympanoplasty patients during the 2013-2019 period in the Hospital's Otolaryngology Service - Victor Lazarte Echegaray.